Brides and young couples: Partners' weight, weight change, and perceptions of attractiveness. (March 2015) - Prichard, Ivanka; Polivy, Janet; Provencher, Véronique; Herman, C. Peter; Tiggemann, Marika; Cloutier, Kathleen
Mate selection seems to be based to some extent on appearance and physique. Assortative mating suggests that romantic partners select each other based on their similarity in important characteristics. Two studies examined the similarity in physiques of members of romantic couples. Study 1 found that the physical measurements of brides-to-be were positively correlated with those of their fiancés, although the brides were lighter and shorter than their partners. The exception was that brides who lost weight before their wedding initially had body mass indexes (BMIs) very similar to their partners. Study 2 also found similarity in weight and BMI between university couple partners. Partners' ratings of the participants' physical attractiveness were higher than participants' own self-ratings, particularly for females. Romantic couples were thus similar in physique and share the same (inaccurate) view of their partners' height and weight. These findings support assortative mating and highlight the importance of weight in the partner selection process.